Takaful as a risk management tool in Islamic estate planning (Journal of Business Management and Accounting, 2012)
Takaful is a form of protection to help us, our family and our beloved person. A good Muslim must be a Muslim with a forward thinking. Hence, some continuity preparation must be done and this preparation must take place from now, in future and in fact after death. To accomplish this goal, wealth management has been determined as an important tool as it plays some important roles to assist for a proper planning in our life and after our death. In other word, Islamic wealth management aims to provide the best reward in this world and hereafter. Furthermore, it has been strengthened by Islamic law that has outlined a comprehensive guidance related to property management after death through a complete and systematic Islamic estate. The benefits can be enjoyed by family from takaful products and will be the Islamic estate of a continuity guarantee after the contributor passes away. Aspired by this issue, this paper focuses on two fold. The first fold discusses on takaful products in Islamic estate planning and followed by the second fold that elaborates on how to incorporate this instrument to be more integrated in Islamic financial system in particular and Islamic economics system in general. The discussions encompasses on shariah aspects and further the applications of this product in Malaysia.